A Mutated Yeast Strain with Enhanced Ethanol Production Efficiency and Stress Tolerance (Atlas Journal of Biology, 2017)
One of the strategies to improve and optimize bio-ethanol production from new feed stocks is to develop new strains of Saccharomyces cerevisiae with tolerance to stresses. The main objectives here were to; generate S. cerevisiae mutants tolerant to high ethanol concentrations; test for their ability to ferment maize starch; and partially characterize the mutations responsible for the new phenotypes. A combination of mutagenesis, selection and cross-stress protection methods were used. EMS (ethyl methanesulfonate) was used to mutagenize one S. cerevisiae strain. The mutagenized yeast strain was exposed to high concentrations of ethanol and tolerant mutants were isolated. Mutants showed improved ethanol yield (0.02-0.03 g/g of maize) and fermentation efficiency (3-5%). Finally, AFLP (Amplified Fragment Length Polymorphism) was performed to identify polymorphisms in the mutants that might underlie the strains ethanol tolerance. The best performing mutant isolate had four altered gene transcripts encoding; an arginine uptake and canavanine resistance protein (CAN1); mitochondrial membrane proteins (SLS1); a putative membrane glycoprotein (VTH1); and cytochrome C oxidase (COX6; EC 1.9.3.1) among about 1,000 tested. It was concluded these mutations might underlie the improved ethanol production efficiency and stress tolerance.